Pengaruh Media Video Youtube Terhadap Motivasi Dan Hasil Belajar Matematika Siswa - Nova Aulia; Beni Asyhar (IAI Muhammadiyah Sinjai, 2022)
The purpose of this study was to determine the effect of the use of YouTube video media on the motivation and learning outcomes of class VIII students at one of MTs in Blitar. The research uses a quantitative approach, the type of research is Quasi Experimental with the Posttest-Only Control Group Design model. Sampling used a purposive sampling technique, with class VIII B as the experimental class and class VIII A as the control class. Data collection techniques using questionnaires, tests, and documentation. Data were analyzed using the independent sample t-test and the MANOVA test with the help of SPSS. The results of the study show that: 1) There is a significant influence of YouTube video media on students' motivation to learn mathematics. Evidenced by the value of Sig. 0.009 <0.05 with an average score of learning motivation in the experimental class of 79.87 and in the control class of 73.97; 2) There is a significant influence of YouTube video media on students' mathematics learning outcomes. Evidenced by the value of Sig. 0.000 <0.05 with an average score of 86.45 in the experimental class and 74.05 in the control class; and 3) There is a significant effect of the use of YouTube video media on students' motivation and learning outcomes in mathematics. Evidenced by the value of Sig. 0.000 < 0.05.